Expression profiling of lncRNAs and mRNAs reveals regulation of muscle growth in the Pacific abalone, Haliotis discus hannai. Issue 1 (December 2018) - Huang, Jianfang; Luo, Xuan; Zeng, Liting; Huang, Zekun; Huang, Miaoqin; You, Weiwei; Ke, Caihuan
Abstract Long non-coding RNAs (lncRNAs) are known to play a major role in the epigenetic regulation of muscle development. Unfortunately there is little understanding of the mechanisms with which they regulate muscle growth in abalone. Therefore, we used RNA-seq to study the muscle transcriptomes of sixHaliotis discus hannai specimens: three large (L_HD group) and three small (S_HD group). We identified 2463 lncRNAs in abalone muscle belonging to two subtypes: 160 anti-sense lncRNAs and 2303 intergenic lncRNAs (lincRNAs). In the L_HD group, we identified 204 significantly differentially expressed lncRNAs (55 upregulated and 149 downregulated), and 2268 significantly differentially expressed mRNAs (994 upregulated and 1274 downregulated), as compared to the S_HD group. The bioinformatics analysis indicated that lncRNAs were relate to cell growth, regulation of growth, MAPK signaling pathway, TGF-β signaling pathway, PI3K-Akt and insulin signaling pathway, which involved in regulating muscle growth. These findings contribute to understanding the possible regulatory mechanisms of muscle growth in Pacific abalone.